Effects of Intrinsic Foot Muscle Training in Improving Stability in Multiple Sclerosis Patients: A Single-Blind Randomized Clinical Trial - Daniel García-García; Jorge Juan Alvarado-Omenat; Rocío Llamas-Ramos; Marta Morais-Quintanilla; Inés Llamas-Ramos (Applied Sciences, 2025)
Background: Stability deficit is one of the most common and disabling signs of multiple sclerosis; therefore, balance training is essential for most patients. Intrinsic foot muscles are a key element in stability, but their influence in multiple sclerosis patients has not been assessed. Objective: The aim of the study was to assess the efficacy of intrinsic foot muscle training on stability in patients with multiple sclerosis. Methodology: A randomized single-blind clinical trial was conducted using a sample of multiple sclerosis patients divided into a control group (CG) and an intervention group (IG). Subjects in the intervention group completed an eight-week intrinsic foot muscles training programme. Static and dynamic stability were measured using the Activities-specific Balance Confidence questionnaire (AsBC), the Four Square Step Test (FSST), the Frailty and Injuries: Cooperative Studies of Intervention Techniques (FICSIT), and the Six Spot Step Test (SSST). Pre- and post-intervention outcomes and differences between groups were calculated. Results: The amount of change comparing pre- and post-intervention results was −0.94 (CG) and 5.59 (IG) in the AsBC questionnaire (p 0.17); −1.0 (CG) and −1.5 (IG) in the FSST (p 0.72); 0.0 for both groups in FICSIT (p 0.629); and −1.5 (CG) and −2.0 (IG) in SSST (p 0.692). Conclusions: Intrinsic foot muscle training produces positive changes in dynamic stability and self-perceived confidence in multiple sclerosis patients.